Efecto del control de sigatoka negra con un fungicida protectante aplicado bajo simulación de lluvia en una plantilla de banano - Ordoñez Pacheco, Jinsoph Armando (2017)
The banana (Musa paradisiaca) at the global level is the fourth most important crop. Ecuador being the main exporter, with an area of approximately 186,222 hectares of banana planted, a production of 6, 529,676 metric tonnes and an average yield per hectare annual production of 36.21 tonnes. At present, the cultivation of banana is affected by the black Sigatoka (Mycosphaerella fijiensis Morelet), a disease that has as taxonomic classification the following: Kingdom: Fungi; Division: Ascomycota; class Dothideomycetes: Capnodiales: Order; and the Family: Mycosphaerellaceae and is considered the most important foliar disease at the global level, which produces losses in performance by up to 100%, if not considered appropriate measures for its management. This disease causes significant disorders in the development of the plant, severely affecting the leaf area and the productivity of the same, by reducing the photosynthetic capacity. The fulfilment of this, the plant fails to remove and carry out the necessary nutrients to the bunch and fill it, presenting premature maturity which causes the fruit does not this act for export. For its control requires a lot of agrochemicals, and it must be borne in mind that the continuous use of a single product or products of the same chemical group promotes the emergence of pathogens resistant to the fungicides used. The use of lower doses at the recommended dose also generates selection pressures that favor the pathogenic strains resistant, resulting in a reduction in the effectiveness of fungicides. According to the foregoing the need arises to implement alternatives that diminish the current problems of quality, productivity and resistance of the pathogen. Incorporating efficient techniques to control the spread of the fungus, the present investigation: as a general objective was to evaluate the fungicide bravo under simulated conditions of rain in a template of bananas, and how specific objectives are determined by the influence of the fungicide for the control of the pinch of the Sigatoka of II and III stage in the sheet 1 and 2; and the assessment of the control by using the amount of hints found in the position of the sheet. Within the methodology was used the variety William, with a planting distance of 2.5 x 2.5 in three rolls. The experimental area was 512 square meters, were 6 treatments with 3 replicates each treatment and a witness, took a random square the same as the one you chose and frame when it was 1.20 meters in height and with 6 functional leaves. The application was made using a CP3 pump, with nozzle 80/02 and took a portion about 5 gallons of product per hectare. The products used were: Bravo 100 cc in 20 liters of water. And how conclusions of the work of research, we have that the fungicide had better effect in the latter stages, on the other hand, in the third stage is very varied, but more frequently in the tips of the leaves. The application is maintained with the same effects up to 28 days, whose treatments were significant on the witness.